Exploring the limits of optics. Issue 11 (November 2017) - Horiuchi, Noriaki
At the 24th General Congress of the International Commission for Optics in Tokyo, photonics-based sensing and simulations were shown to benefit research into phenomena that span the nanometre to astronomical range.